Ozone Impact on Emission of Biogenic Volatile Organic Compounds in Three Tropical Tree Species From the Atlantic Forest Remnants in Southeast Brazil - Moura, Bárbara Baêsso; Bolsoni, Vanessa Palermo; de Paula, Monica Dias; Dias, Gustavo Muniz; de Souza, Silvia Ribeiro (Frontiers in Plant Science, 2022)
Plants emit a broad number of Biogenic Volatile Organic Compounds (BVOCs) that can impact urban ozone (O3) production. Conversely, the O3 is a phytotoxic pollutant that causes unknown alterations in BVOC emissions. In this sense, here we characterized the constitutive and O3-induced BVOCs for two (2dO3) and four (4dO3) days of exposure (O3 dose 80 ppb) and evaluated the O3 response by histochemical techniques to detect Programmed cell death (PCD) and hydrogen peroxide (H2O2) in three Brazilian native species. Croton floribundus Spreng, Astronium graveolens Jacq, and Piptadenia gonoacantha (Mart.) JF Macbr, from different groups of ecological succession (acquisitive and conservative), different carbon-saving defense strategies, and specific BVOC emissions. The three species emitted a diverse BVOC composition: monoterpenes (MON), sesquiterpenes (SEQ), green leaf volatiles (GLV), and other compounds (OTC). C. floribundus is more acquisitive than A. graveolens. Their most representative BVOCs were MeSA (OTC), (Z) 3-Hexenal, and (E)-2-Hexenal (GLV), γ-Elemene and (-)-β-Bourbonene (SEQ) β-Phellandrene and D-Limonene (MON), while in A. graveolens were nonanal and decanal (OTC), and α-pinene (MON). P. gonoachanta is more conservative, and the BVOC blend was limited to MeSA (OTC), (E)-2-hexenal (GLV), and β-Phellandrene (MON). The O3 affected BVOCs and histochemical traits of the three species in different ways. C. floribundus was the most O3 tolerant species and considered an SEQ emitter. It efficiently reacted to O3 stress after 2dO3, verified by a high alteration of BVOC emission, the emergence of the compounds such as α-Ionone and trans-ß-Ionone, and the absence of H2O2 detection. On the contrary, A. graveolens, a MON-emitter, was affected by 2dO3 and 4dO3, showing increasing emissions of α-Pinene and β-Myrcene, (MON), γ-Muurolene and β-Cadinene (SEQ) and H2O2 accumulation. P. gonoachanta was the most sensitive and did not respond to BVOCs emission, but PCD and H2O2 were highly evidenced. Our results indicate that the blend of BVOC emission in combination with histochemical is a powerful tool to confirm the species tolerance to O3. Furthermore, our findings suggest that BVOC emission is a trade-off associated with different resource strategies of species indicated by the changes in the quality and quantity of BVOC emission for each species.